A semi-quantitative Risk assessment method in process plants: confined spaces - Salvina Mure; Gianfranco Camuncoli; Micaela Demichela (Chemical Engineering Transactions, 2019)
The purpose of the present work was to develop a methodology for the confined spaces risk assessment in the workplace. Within the technological risk function, R=PxD, in order to account for the specific features of confined spaces, the probability of occurrence P was defined in two indices: the frequency of exposure to confined spaces, F, and the contact time I (strictly related to the complexity of the intervention that must be performed). The damage M has been separated into specific parameters considering the energy, the environment and the geometry of the confined space under examination, and in detail:an incorrect or not correctly signalled insulation that may lead to a sudden operation of part of the system with consequent accidental leakage of fluids or substances inside the confined space and / or movement of any mechanical part, with the energy damage factor DE;the atmosphere present in the confined space, which may be poorly oxygenated, corrosive, harmful, toxic or potentially explosive, with the environment damage factor DA. Moreover, as a specific corrective factor of damage factors, the criticality of the physical and geometrical characteristics of the confined space is evaluated, considering how it's easy for the worker to leave the confined space or to be rescued if he feels bad, with the factor of FCDG geometry damage correction. Once the damage factors have been identified and corrected with the FCDG factor, the specific risks of the confined space are evaluated by multiplying each damage factor by the probability of occurrence P, thus obtaining the index of:Risk of contact with hazardous substances or with moving mechanical parts;Asphyxiation risk;Chemical risk;Risk of fire and explosion. The application of this method to the confined spaces of a real process plant allowed to validate the methodology.